2021
DOI: 10.1038/s41598-021-90620-w
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, physicochemical, and microstructural properties of asphalt binder modified by fumed silica nanoparticles

Abstract: Warm mix asphalt (WMA) is gaining increased attention in the asphalt paving industry as an eco-friendly and sustainable technology. WMA technologies are favorable in producing asphalt mixtures at temperatures 20–60 °C lower in comparison to conventional hot mix asphalt. This saves non-renewable fossil fuels, reduces energy consumption, and minimizes vapors and greenhouse gas emissions in the production, placement and conservation processes of asphalt mixtures. At the same time, this temperature reduction must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Therefore, this condition was discarded and not considered a good representation option. The above coincides as described by Saha and Biligiri [38] since the increase in temperature can reduce the elastic properties of the binder, which becomes viscous [19], while the reduction in temperature decreases the performance of the asphalt mix [42], which makes the binder brittle and the asphalt mix vulnerable to cracking [12,19]. For specimens tested at a temperature of 20 • C (see Figure 5c) at different load application rates, it was observed that the specimens adopted both components of the asphalt material (elastic and plastic), thus presenting a quasi-fragile behavior, which was ideal for evaluating cracking, as it was consistent with the objective of representing the real conditions to which a flexible pavement is subjected.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, this condition was discarded and not considered a good representation option. The above coincides as described by Saha and Biligiri [38] since the increase in temperature can reduce the elastic properties of the binder, which becomes viscous [19], while the reduction in temperature decreases the performance of the asphalt mix [42], which makes the binder brittle and the asphalt mix vulnerable to cracking [12,19]. For specimens tested at a temperature of 20 • C (see Figure 5c) at different load application rates, it was observed that the specimens adopted both components of the asphalt material (elastic and plastic), thus presenting a quasi-fragile behavior, which was ideal for evaluating cracking, as it was consistent with the objective of representing the real conditions to which a flexible pavement is subjected.…”
Section: Resultssupporting
confidence: 79%
“…Water filtration and the addition of air, an oxidation process, is generated in the mixture as the number of voids increases [ 31 , 32 ], accelerating the aging processes of the pavement and increasing its fragility, decreasing its fracture resistance [ 33 , 34 ], and increasing the probability of cracking failure due to thermal changes [ 35 , 36 ]. Therefore, environmental agents can change the mechanical characteristics of the pavement [ 37 ]; as the temperature decreases, the mixture becomes stiffer, reducing its elasticity [ 38 , 39 ] and making it prone to cracking more than less stiff ones [ 40 , 41 , 42 , 43 ]. This is because temperature impacts the viscoelastic and stress state behavior, resulting in fracture initiation or propagation [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of the bitumen, many different additives have been added to it, such as polymers, fibers, and nanomaterials. Goshtasp et al introduced a new nanocomposite bitumen binder, which was modified by clay/fumed silica nanoparticles. The new binder showed higher mechanical, chemical, and thermal improvements than the conventional bitumen. In addition, the results indicated that the composite can significantly disrupt chemical oxidation and decomposition and delay aging.…”
Section: Introductionmentioning
confidence: 99%
“…Under the repeated action of the traffic load and temperature load, the asphalt surface layer tends to expand and form reflection cracks [8][9][10][11], which seriously affects the road's performance and shortens its life. At the same time, the performance of commonly used road cementing materials is greatly affected by the environment, and their mechanical properties are relatively complex, which further aggravates the occurrence of pavement crack disease [12][13][14]. As a kind of thick asphalt concrete pavement structure with a broad development prospect in recent years, the full-depth asphalt pavement [15][16][17][18] has unique advantages compared with other types of pavement, which are generally made of modified asphalt and recycled asphalt [19][20][21] as pavement asphalt materials.…”
Section: Introductionmentioning
confidence: 99%